2021
DOI: 10.1001/jama.2021.16628
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Vasopressin and Methylprednisolone vs Placebo on Return of Spontaneous Circulation in Patients With In-Hospital Cardiac Arrest

Abstract: IMPORTANCE Previous trials have suggested that vasopressin and methylprednisolone administered during in-hospital cardiac arrest might improve outcomes.OBJECTIVE To determine whether the combination of vasopressin and methylprednisolone administered during in-hospital cardiac arrest improves return of spontaneous circulation. DESIGN, SETTING, AND PARTICIPANTS Multicenter, randomized, double-blind, placebo-controlled trial conducted at 10 hospitals in Denmark. A total of 512 adult patients with in-hospital card… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
104
2
1

Year Published

2022
2022
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 82 publications
(107 citation statements)
references
References 34 publications
(80 reference statements)
0
104
2
1
Order By: Relevance
“…3 a, combination therapy with VSE could not significantly increase the survival ratio (OR: 2.082, 95% CI: 0.638–6.796, P value = 0.225), while the heterogeneity was reported to be high (Cochrane Q test: I 2 = 78.52%, P value = 0.010). Sensitivity analysis showed that Andersen et al study [ 26 ] had an impact on the rate of hospital mortality; however, they did not affect the significance of the results (OR: 2.082, 95% CI: 0.638–6.796, P value = 0.225).
Fig.
…”
Section: Resultsmentioning
confidence: 88%
See 4 more Smart Citations
“…3 a, combination therapy with VSE could not significantly increase the survival ratio (OR: 2.082, 95% CI: 0.638–6.796, P value = 0.225), while the heterogeneity was reported to be high (Cochrane Q test: I 2 = 78.52%, P value = 0.010). Sensitivity analysis showed that Andersen et al study [ 26 ] had an impact on the rate of hospital mortality; however, they did not affect the significance of the results (OR: 2.082, 95% CI: 0.638–6.796, P value = 0.225).
Fig.
…”
Section: Resultsmentioning
confidence: 88%
“…After assessment of full texts of the studies, 17 papers were also excluded from further evaluation, because of irrelevant population and the type of studies. A total of three RCTs were eligible for including in the current systematic review and meta-analysis, carried out on 869 subjects [ 26 28 ]. The PRISMA flow diagram for screening inclusion/exclusion criteria in identification of the related papers is illustrated in Fig.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations